Analysis of Officer Behavior in Achieving Minimum Service Standards for the Diabetes Mellitus Control Program at the Lombok Regional Health Center - Sofianingrum, Arnita; Astriani, Iis; Andi, Muhammad Alwi; Doni, Lalu Putram (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Diabetes Mellitus (DM) is a disease in which blood sugar levels exceed the normal threshold. DM in Indonesia has increased by 10% from 15% to 25%, and 40-50% of people with heart disease are also diabetes mellitus sufferers. The aim of this research is to determine the description of the behavior of officers in achieving minimum service standards for the Diabetes Mellitus control program at the West Lombok Regional Health Center. The results of the research show that the achievement of Minimum Service Standards (SPM) in the DM program at the West Lombok Regional Health Center has not met the Government's target. Lack of achievement of SPM can cause an increase in the number of DM cases that are not recorded and affect the achievement of existing health targets at the district and national level.